Modification of Poly(lactic acid-co-glycolic acid) Film via Blending with Polyacrylonitrile - Zhu, Guo-Quan; Wang, Fa-Gang; Xu, Ke-Jing; Gao, Qiao-Chun; Liu, Yu-Ying (Asian Journal of Chemistry, 2014)
A series of poly(lactic acid-co-glycolic acid) (PLGA)/polyacrylonitrile blend films with different polyacrylonitrile mole content were prepared by casting the polymer blend solution in dimethyl sulfoxide. Surface morphologies of the PLGA/PAN blend films were studied by scanning electron microscopy. Thermal, mechanical, and chemical properties of PLGA/PAN blend films were investigated by differential scanning calorimeter, tensile tests and surface contact angle tests. It was displayed that the introduction of polyacrylonitrile could greatly modify the properties of PLGA films.